Attitude changes of cancer pain and opioids among cancer patients: a cross-sectional study spanning a decade - Juan Wu; Gui-Xia Wei; Lin-Juan Li; Yu-Wen Zhou; Jia-Ling Wang; Yi-Xiao Bai; Cong-Jun Li; Meng Qiu (BMC Cancer)
Abstract Objectives A comprehensive understanding of attitudes and changes in attitudes towards cancer pain and opioid analgesics among cancer patients can help healthcare professionals to provide more targeted and effective health education to improve the quality of care and health education for patients with cancer pain. Methods A cross-sectional study was conducted from January 2013 to December 2013 and from January 2023 to December 2023, respectively. Questionnaires were used to collect data, including the clinical characteristics of patients and their perspectives on cancer pain and opioids. A propensity score matching (PSM) analysis was performed to balance the baseline characteristics. Results A total of 894 patients were enrolled in this study, 474 patients in 2013 and 420 patients in 2023. After PSM, 600 patients were included in this analysis. Over the course of a decade, an increasing number of patients were able to accept cancer pain management, opioid medication, and adverse events of opioids. With regard to opioid analgesics, patients’ primary concern had shifted over the decade from addiction to the analgesic effect of opioids. Although understanding of opioids had improved over a decade, the vast majority of the population was still poorly informed about opioids. In addition, approximately 90% of participants believed that their education about opioids was insufficient. Conclusions Over a decade, although patients had more positive attitudes towards cancer pain management, their knowledge and health education about cancer pain was poor. This finding suggests that health professionals should work together to disseminate knowledge about cancer pain and strengthen health education to manage cancer pain well and improve the quality of life of cancer patients.